Genotypes of ITS region of rRNA in Microcystis (Cyanobacteria) populations in Erhai Lake (China) and their correlation with eutrophication level. (22nd June 2015) - Song, Gaofei; Jiang, Yongguang; Yu, Gongliang; Li, Renhui
<x xml:space="preserve">Abstract</x> Previous studies on spatiotemporal changes of Microcystis genotypes have shown that the existence and succession of dominant genotypes always occur in eutrophicated freshwater bodies. However, few studies have focused on the correlation between genotype composition and eutrophication level. In the present study, clone libraries of the internal transcribed spacer (ITS) of rrn operon were sequenced from Microcystis populations in Erhai Lake, a subtropical plateau lake in the preliminary eutrophication stage. The genotype composition of the Microcystis populations was highly variable at spatiotemporal scales, and 473 ITS genotypes were identified from the 800 ITS sequences obtained. However, no significantly dominant ITS genotypes existed in the lake. Comparison of Erhai Lake with four major lakes in China, namely, Taihu, Chaohu, Gucheng, and Shijiu Lakes, showed that the Microcystis ITS genotypes and genetic diversity were negatively correlated with eutrophication level. Extensive comparison of the Microcystis ITS genotypes from waters worldwide revealed that 440 ITS genotypes were unique to Erhai Lake, and no obvious phylogenetic correlations can be detected among the dominant genotypes from different water bodies. The high genetic diversity of the Microcystis populations in Erhai Lake may have resulted from the effect of the early stage of eutrophication.